2023
DOI: 10.1007/s11605-023-05607-x
|View full text |Cite
|
Sign up to set email alerts
|

Length of the Remnant Cystic Duct and Bile Duct Stone Recurrence: a Case‒Control Study

Abstract: Background Since the introduction of the Critical View of Safety approach in laparoscopic cholecystectomy, exposure of the common bile duct, and common hepatic duct is not recommended, therefore, the length of the cystic duct remnant is no longer controlled. The aim of this case‒control study is to evaluate the relationship between the length of the cystic duct remnant and the risk for bile duct stone recurrence after cholecystectomy. Methods All MRIs with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…2 Risk factors for post-cholecystectomy choledocholithiasis (PCC) are long cystic duct stump and SC or IC. [3][4][5] A study of 362 patients who had undergone a laparoscopic cholecystectomy (LC) for benign disease had a PCC incidence of 23.5%. The authors found a median cystic duct stump length on MRI of 31mm or greater was a significant risk factor for PCC.…”
Section: Discussionmentioning
confidence: 99%
“…2 Risk factors for post-cholecystectomy choledocholithiasis (PCC) are long cystic duct stump and SC or IC. [3][4][5] A study of 362 patients who had undergone a laparoscopic cholecystectomy (LC) for benign disease had a PCC incidence of 23.5%. The authors found a median cystic duct stump length on MRI of 31mm or greater was a significant risk factor for PCC.…”
Section: Discussionmentioning
confidence: 99%
“…Esta condición puede llevar al desarrollo de colecistitis, y por consecuencia requerir manejo quirúrgico 1 . La colecistectomía laparoscópica es una de las cirugías más frecuentemente realizadas por el cirujano general, en Estados Unidos se realizan anualmente más de 750.000 colecistectomías 2 , además se considera el tratamiento de elección para el manejo de los pacientes con colecistitis 3,4 .…”
Section: Introduccionunclassified